Enterprise JavaBeans - Monson-Haefel, Richard (Java series (O'Reilly & Associates), 2000)
"Enterprise JavaBeans, Second Edition, is the definitive guide to EJB 1.1, which incorporates the latest developments in EJB technology. Enterprise JavaBeans allows you to build complex, mission-critical systems using snap-together software components that model business objects and processes. EJB greatly simplifies the process of development by taking care of issues like object persistence, security, and transaction management."